The association between depression and thyroid function - Ma, Yuhui; Wang, Miao; Zhang, Zhishen (Frontiers in Endocrinology, 2024)
Emerging evidence indicated that depression is currently one of the most burdensome diseases worldwide and it can lead to a variety of functional physical impairments. However, the studies estimated the association between depression and thyroid function remain sparse. We aimed to investigate the association between depression and thyroid function in the American population. A cross-sectional analysis was performed using the data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2007 to 2012. In the 12502 adults aged 20-80, weighted linear regression models and multiple logistic regression models were applied to evaluate the association between depression and thyroid function indicators. The thyroid indicators investigated were mainly free thyroxine (FT4), total T4 (TT4), free triiodothyronine (FT3), total T3 (TT3), thyroid-stimulating hormone (TSH), and antithyroperoxidase antibody (TPOAb), Thyroglobulin (Tg) and antithyroglobulin antibody (TgAb). The final results were reached after adjusting for various confounding factors. In the stratification analysis of subgroups divided by age, depression was significantly negatively correlated with FT4, FT3, and TT3 in both younger adults (p = 0.00122, <0.00001, 0.00003) and older adults (p = 0.00001, 0.00004, <0.00001). In contrast, depression was significantly negatively correlated with TT4, TPOAb, and Tg in older adults (p = 0.00054, 0.07083, 0.00695) and positively correlated in younger adults (p = 0.01352, 0.00488, <0.00001). The subgroup analysis by gender revealed that depression was significantly negatively correlated with FT4, FT3, and TT3 in both adult males (p = 0.0164, 0.0204, 0.0050) and adult females (p = <0.0001, <0.0001, <0.0001 ), which was more prominent in females. The positive correlation between depression symptoms and TPOAb was only found in adult females (p = 0.0282). This study confirmed a significant correlation between depressive and thyroid function and it varied among different genders or iodine concentrations. In the future, more prospective studies are needed to reveal these findings and confirm a causal relationship between them.